Altered neural function in pediatric bipolar disorder during reversal learning - Dickstein, Daniel P (2010)
OBJECTIVE: Data documenting the functional impairment associated with the diagnosis of bipolar disorder (BD) in children and adolescents highlight the need for greater understanding of its pathophysiology. Toward that end, we demonstrated previously that BD youth have behavioral deficits on reversal learning tasks. On such tasks, participants must first acquire a stimulus/response relationship through trial-and-error learning, and then discern when the stimulus/reward relationship reverses. Here, we use event-related functional magnetic resonance imaging (fMRI) to elucidate neural correlates of reversal learning deficits in euthymic BD youth compared to typically developing controls. METHOD: We compared euthymic pediatric BD participants (n = 16) versus age-, sex-, and IQ-matched controls (n = 16). Our main outcome measure was blood oxygen level-dependent (BOLD) signal measured with fMRI during an event-related probabilistic reversal task. RESULTS: Pediatric BD participants had significantly greater neural activity than controls in fronto-parietal regions during the reversal phase, particularly in response to punished reversal errors (p < 0.05 corrected for multiple comparisons). CONCLUSIONS: Our current study suggests that during reversal learning, BD youths inefficiently recruit regions associated with processing response conflict and implementing alternative responses, including subdivisions of the frontal cortex and the parietal cortex. Such deficits are present in euthymic BD youth. Further work is necessary to evaluate the specificity of such alterations.